The Effect of Information Technology, HR Competence, Internal Control, and Organizational Culture on the Quality of Financial Reports - Suhardi (Institut Bisnis dan Informatika Kesatuan, 2025)
This study investigates the influence of Human Resource (HR) competence, Internal Control Systems (ICS), Information Technology (IT) utilization, and organizational behavior on the quality of financial statements in local governments, with public accountability as a mediating variable. It aims to understand how these factors enhance transparency and compliance in financial reporting. A quantitative approach was employed, using a survey of 200 local government officials, selected via purposive sampling. Data were collected through questionnaires and analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS), testing direct and mediated effects of the variables on financial statement quality. HR competence, ICS, IT utilization, and organizational behavior significantly improve financial statement quality. Public accountability directly enhances quality and mediates the effects of HR competence, ICS, IT utilization, and organizational behavior, all with p < 0.05, confirming all hypotheses. The findings advance Agency Theory and related frameworks by highlighting public accountability’s mediating role. Practically, local governments can improve financial reporting by enhancing HR training, strengthening ICS, adopting IT systems, and fostering transparent cultures, offering a model for improved governance and public trust.